Effect of organic mulching and irrrigation schedule through drip on growth and yield of ’lat Sundari’ mango (Mangifera indica) in eastern region of India - Kumar, Dinesh; Pandey, V; Nath, Vishal (The Indian Journal of Agricultural Sciences, 2008)
The field experiment on organic mulching in combination with irrigation schedule through drip on 5-years-old mango (Mangifera indica L.) plants was started during 2002 03 and continued up to 2006-07 at Bhubaneswar. Five treatments, viz. organic mulching + 25% pan evaporation replenishment (PER) , organic mulching.+ 50% PER , organic mulching + 75% PER, organic mulching only and rainfed control with 5 replications were maintained under randomized block design. Experimental results clearly indicated that organic mulching coupled with drip irrigation schedule improved growth and bearing of mango. Significantly maximum canopy volume (77.82 m3), fruit number (530.45) and yields (86.40 kg/tree) were recorded due to organic mulching + 50 % PER. The fruit quality attributes, such as fresh fruit weight (248.37 g), fruit dry weight (48.25 g) and pulp weight were maximum due to organic mulching + 75% PER. Total soluble solids was higher in organic mulching + 25% PER but differences were found non-significant among different treatments. Maximum soil moisture content was recorded due to organic mulching + 75% PER. Minimum canopy volume, fruit number, yield, quality of fruit and soil moisture content were observed in rainfed control plants.